The development of the law of the sea in relation to Malaysia - M. Yatim, Zakaria (Universiti Utara Malaysia, 1992)
Freedom of the seas existed during the Melaka Sultanate. When the Portugese and leter the Dutch occupied Melaka, the seas were treated as mare clausum. The concept of the territorial sea was evolved during British Colonial period. Conventional rules of the law of the sea applied to Malaysia by accessions to the relevant conventions. The law of the sea also developed through unilateral claims, bilateral treaties and legislations. The Statement relating to Article 233 of the Convention on the law of the sea may develop into a special legal regime perculiar to the Straits of Malacca and Singapore.